Access to health professionals by children and adolescents with mental disorders: Are we meeting their needs?. (October 2018) - Sawyer, Michael G; Reece, Christy E; Sawyer, Alyssa CP; Johnson, Sarah E; Hiscock, Harriet; Lawrence, David
Objective: To identify the percentage of 4–17 year olds with mental disorders in Australia who attended health professionals for single or repeat visits to get help for emotional and behavioural problems during a 12-month period. To identify factors associated with single and repeat visits, and the average length of time between visits. To compare the number of parent-reported visits with visits recorded in the Medicare Benefits Schedule. Method: The study used data from the national survey of the mental health and wellbeing of 4–17 year olds conducted in 2013–2014 ( n = 6310). Participants were randomly selected from all 4 to 17 year olds in Australia. Information about visits was available from face-to-face interviews with parents, the Medicare Benefits Schedule and self-reports from 13 to 17 year olds. Mental disorders were assessed using the Diagnostic Interview Schedule for Children Version IV completed by parents. Results: Parents reported that 51.1% of 4–17 year olds with mental disorders had attended a health professional during the previous 12 months. However, 13.6% of these children had attended on only a single occasion, most commonly with a general practitioner. With the exception of occupational therapists, 2–4 visits was the most common number of repeat visits. Children with comorbid disorders and severe functional impairment and those aged 12–17 years were more likely to have repeat visits. Among those with linked Medicare Benefits Schedule data, more children were reported by parents to have attended Medicare Benefits Schedule-funded health professionals (47.9%) than were recorded in Medicare Benefits Schedule data (38.0%). Conclusion: The typical number of visits to health professionals by children with mental disorders during a 12-month period is relatively small. Furthermore, parent-reports may overestimate the number of visits during this time. It seems unlikely that current patterns of attendance are of sufficient duration and frequency to allow full implementation of evidence-based treatment programmes for child and adolescent mental disorders.